Prevalence, Physiological Determinants, and Antibiotic Susceptibility Patterns of Staphylococcus aureus Nasal Carriage among Healthcare Workers: A Hospital-Based Public Health Study - Adina Qaiser, Afshan Zia, S. M. Qaisar Sajjad, Muhammad Tahir Shah, Hamid Nawaz Khokhar,Syeda Nosheen Zehra, Aqeela Kousar, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Staphylococcus aureus nasal carriage among healthcare workers represents a major public health concern because colonized individuals serve as silent reservoirs for hospital-acquired infections. Understanding prevalence, physiological determinants, and antibiotic susceptibility patterns is essential for designing targeted infection-control strategies. Objective: To determine the prevalence of Staphylococcus aureus nasal carriage among healthcare workers, assess associated physiological determinants, and evaluate antibiotic susceptibility patterns of isolated strains. Methods: This cross-sectional study was conducted from June 2022 to June 2023 in the Department of Pathology at Sharif Medical and Dental College, Lahore, Sahara Medical College, Narowal, and Sir Syed College of Medical Sciences for Girls, Karachi, Pakistan. A total of 100 healthcare workers were recruited through convenience sampling. Nasal swabs were collected aseptically from the anterior nares and cultured on mannitol salt agar. Staphylococcus aureus was confirmed using Gram staining, catalase testing, coagulase testing, and DNase testing. Antibiotic susceptibility was evaluated using the Kirby–Bauer disk diffusion method following Clinical and Laboratory Standards Institute guidelines. Demographic and physiological variables including body mass index, allergic rhinitis, deviated nasal septum, and night-shift duties were recorded and analyzed for association with colonization. Results: The prevalence of Staphylococcus aureus nasal carriage was 34 percent, with 12 percent identified as methicillin-resistant Staphylococcus aureus. Colonization was significantly higher among individuals with elevated body mass index, allergic rhinitis, deviated nasal septum, and those working night shifts. High resistance was observed to penicillin and azithromycin, while all isolates remained sensitive to vancomycin and linezolid. Conclusion: Staphylococcus aureus nasal carriage remains common among healthcare workers and is strongly influenced by physiological and occupational factors. Continuous surveillance, decolonization strategies, and antimicrobial stewardship are essential to reduce transmission risk in healthcare settings. Keywords: Staphylococcus aureus, nasal carriage, healthcare workers, physiology, antibiotic susceptibility, MRSA, public health.